Using Rasch Analysis to Develop Multi- representation of Tier Instrument on Newton’s law (MOTION) - Samsudin, Achmad; Fratiwi, Nuzulira Janeusse; Ramalis, Taufik Ramlan; Aminudin, Adam Hadiana; Costu, Bayram; Nurtanto, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to develop Multi-representation of Tier Instrument on Newton’s law (MOTION) using Rasch analysis. This instrument can be used to diagnose students’ conceptions, especially on Newton’s laws. Multi-representation of tier instrument also can be used for three forms of tests (pre-, post- and delayed test), thus students do not realize they have done the same problem. The research method was used ADDIE (Analyse, Design, Develop, Implement and Evaluation) model. The participants were students at one of senior high school at Sukabumi. West Java, as much as 92 students (41 male students and 51 female students, with an average age of 15-17 years) who were in K-11. At evaluating stage, all students’ answers were analysed based on the student’s conception category, scored, then evaluated using Rasch analysis with Winstep 4.4.5 software. The data analysis including validity and reliability of MOTION. Based on the Rasch analysis, it can be concluded that MOTION was valid and reliable to use, although there are a few questions that need to be minor revised. Other researchers can use MOTION to diagnose students’ conceptions of Newton’s law material and can also use Rasch analysis to develop a research instrument.